Identities I - Cuypers, Kris; Fol, Carine; Hoet, Jan (Geel : CC de Werft Cultuurcentrum Geel, 2007)
Beeckman, Vincen ; Beuys, Joseph ; Blockx, Paul ; Bourgeois, Louise ; Cats, Florence ; Cycon, Kaziemierz ; Duhem, Paul ; Dumarey, Marcella ; François-Gil ; Guns, Patrick ; Lopez-Menchero, Emilio ; Michiels, Jozef ; Nedjar, Michel ; Orlan ; Poladian, Vahan ; Sciandra, Vincenzo ; Scott, William ; Targa ; Theate, Dominique ; Walla, August
Nederlands
Frans
Exhibition. Identities I. Geel. De Halle Geel. CC de Werft Cultuurcentrum Geel, 25.03.2007 - 03.06.2007.
boek